Parents and Educator’s Perceptions to Sex Education and HIV/AIDS in Primary Schools in the Motheo District - Ntlhare, Leetwane; Phindane, Pule (Journal of Human Ecology, 2017)
This paper investigated the perceptions of parents and Foundation Phase educators on whether Foundation Phase learners have the rights to be educated about HIV/AIDS and sex education before they reach adolescent stage. Twenty Foundation Phase educators and twenty parents were sampled in this research. Qualitative and quantitative research methods were used to collect data. The findings showed that parents and educators agreed that children are prisoners of their own environment and recognize the right of the child to be protected. Support from different stakeholders and adequate materials should be provided for the successful implementation of the Life Skills programs. The implications of this study are discussed.
Published Article
Keywords: Foundation Phase Educators; Learners; Sex Education; HIV/AIDS